Implementasi Peraturan Pemerintah Nomor 39 Tahun 2021 tentang Penyelenggaraan Bidang Jaminan Produk Halal - Muhammad Adi Riswan Al Mubarak; Lola Malihah; Mu’minah Mu’minah; Muhammad Yulian Ma’mun (Al-Adl : Jurnal Hukum, 2023)
This paper aims to assess the importance of implementing halal certification from the side of producers and consumers. This research activity uses the method of literature study. The conclusion of this research shows the importance of this certification for producers because it is very beneficial for product continuity. Meanwhile, for consumers, this certification is beneficial in protecting consumers from all materials that are hazardous to health and all matters related to the halal product, both in terms of ingredients and processing methods. Halal certification also eliminates doubts about the product to be consumed. Initially, this halal certification was only voluntary or the producer's desire (voluntary), yet to be supported by strong Law, but now it has become an obligation (mandatory) for producers. The implementation procedure has involved many related parties, from institutions and ministries, and even at the international level, cooperation has also been carried out regarding this halal certificate. The implementation is currently based on digitization, namely the SIHALAL application. PP No 39 of 2021, concerning the Implementation of the Halal Product Assurance Sector, is clear enough to spell out the mandates of the Halal Product Assurance Law and the Job Creation Law. However, there must be something that needs to be finalized to improve the implementation of other halal product guarantees.